Dinâmica do oxigênio dissolvido no estuário do rio do Sal/Sergipe - Santos, Tâmara Tatiana Souza (2014)
The River Sal estuary is part of the Sergipe river basin and receives sanitary sewage disposal in natura, several housing projects and also industrial and aquaculture activities discharges. The study area is located in the city of Aracaju, capital of Sergipe, northeastern Brazil. In the sampling campaigns, conducted in the period of October / 2010 to January / 2014, surface water samples for the following parameters were taken in ten points distributed along the estuary and in each sample analyzed: temperature, pH, salinity, dissolved oxygen (DO), total phosphorus, nitrate, nitrite, the total ammonia nitrogen, total reactive phosphorus and total dissolved organic carbon. The pH ranged from 7.0 to 8.6 and the salinity from 6.69 to 26.22. The environment had a high concentration of nutrients, phosphorus (total phosphorus and phosphate) and nitrogen (nitrate and ammonia), with values generally above the limits recommended by CONAMA Resolution 357, to brackish waters. Average concentrations of dissolved organic carbon ranged from 6.05 ± 3.63 to 12.42 ± 2.62 mg L-1, indicating an environment highly impacted by organic matter originating from anthropogenic sources, predominantly domestic sewage, but also with contributions from other sources, probably associated with the disposal of aquaculture activities. The spatial and temporal distribution of the DO was very heterogeneous, being identified three distinct periods: October 2010 with higher average concentrations (13.60 ± 3.28 mg L-1); April, July and September 2011 and September 2013 with intermediate concentrations (9.04 ± 2.83 mg L-1) and December / 2010, February / 2011, November 2013 and January 2014 with the lowest concentrations (4, 09 ± 0.7 mg L-1). There were events of hypoxia, being more pronounced in December 2010, when all the initial part of the estuary was reached (40% of all measured DO), but no evidence of fish mortality were identified. The results of the study period suggest that the dynamics of oxygen in the estuary of the River Sal is determined primarily by allochthonous input of organic matter, which requires the water to the dissolve oxygen for oxidation. The spatiotemporal distribution indicates that the highest probability for hypoxia phenomena occur, including fish kills, is in the dry season (November to February) and in areas downstream Palame and Poço do Mero.